Candombe afrouruguayo, los pies atados al latido del corazón (2024)
Mayté Álvarez Ropaín's relationship with diverse musical training spaces, both formal and nonformal and informal, has allowed her, being Colombian, to find a niche within what she calls the cultural universe of Afro-Uruguayan candombe. The fact that her personal history around AfroUruguayan candombe becomes her object of study has allowed her to measure the importance of (i) getting involved in the aforementioned universe as a percussionist performer of a family of drums, and (ii) being admitted in a way privileged in a community of knowledge, in what, in her analysis, she calls a “permission” from the bearer community, to be the transmitter of that knowledge that goes beyond musical expression and becomes living appropriation. From there, she develops two important objectives: the first, to unravel how she could become a transmitter, how it has also been possible for her to generate reproduction of her knowledge about candombe, what are the keys that she appropriated throughout her life, how, In his own words, his feet were tied to the beat of a collective heart of which he is already a part; that of a community from another Latin American latitude that, in the midst of submission, in resistance, carries under its sore skin a great wealth of expressions of which it is the guardian